Enhancing Logical Thinking and Learning Interest through Open-Ended Approaches and Supportive Learning Environments in Mathematics Education - Lailatul Hoyali; Syaharuddin; Vera Mandailina (Mimbar Ilmu, 2025)
The low logical thinking skills and learning interest in mathematics have become a major issue in the students’ learning process. This study aims to analyze the effect of open-ended approaches and supportive learning environments on students’ logical thinking skills and learning interest in mathematics. This research employs an experimental design with a quasi-experimental approach. The subjects consisted of students divided into experimental and control groups. Data were collected using logical thinking tests, learning interest questionnaires, and learning environment observations as research instruments. Data analysis was performed using multiple linear regression, t-tests, and N-Gain analysis. The results indicate that simultaneously, open-ended approaches and supportive learning environments have a significant effect on logical thinking skills (R² = 66.6%; p = 0.000) and learning interest in mathematics (R² = 37.5%; p = 0.009). Individually, the open-ended approach positively affects logical thinking skills (B = 0.789) but negatively influences learning interest (B = -0.482), while the learning environment positively contributes to both. The t-test revealed a significant improvement in logical thinking skills in the experimental group compared to the control group (p = 0.001), and N-Gain analysis reinforced these findings by showing higher and more consistent learning outcomes in the experimental class. The study concludes that a combination of open-ended approaches and supportive learning environments is effective in enhancing students’ cognitive and affective aspects. The study’s implications emphasize the importance of teachers considering student readiness and creating a supportive learning environment to optimize and enrich mathematics learning experiences.